Influence of WDR41 and ANKRD31 gene polymorphism on udder and teat type traits and mastitis in Karan Fries cows - SHARMA, NISHA; D, REVANASIDDU; KUMAR, SUSHIL; SINHA, BEENA; KUMARI, RAGINI; GUPTA, I D; VERMA, ARCHANA (The Indian Journal of Animal Sciences, 2022)
In the present study, the effect of genetic polymorphism of WD-repeat containing protein 41 (WDR41) and Ankyrin repeat domain containing protein 31 (ANKRD31) gene on 17 traits related to udder and teat type and mastitis in 123 Karan Fries cows was studied. Restriction Fragment Length Polymorphism (RFLP) was used to identify the SNP (410 bp and 475 bp) in PCR amplified product of intron 4 and exon 10 in WDR41 gene. Both of them were polymorphic with Guanine to Adenine transition, and three genotypes namely AA, AG and GG were observed. In ANKRD31 gene, RFLP was used to identify the SNP in 513 bp PCR amplified product of intron 24 and two SNPs were found. We report for the first time that intron 4 and exon 10 of WDR41 gene is significantly associated with udder depth (UD), udder balance (UB), central ligament (CL), teat circumference (TC), SFF and tear diameter (TD), rear udder width (RUW), and mastitis. SNP rs110012582 in intron 24 of ANKRD31 gene is associated significantly with UD, distance between left and right teat (DLR), SFF, and SNP rs473512406 with udder length (UL), udder width (UW), udder circumference (UC), fore teat length (FTL), rear teat length (RTL), distance between fore and rear teat (DFR), DLR and mastitis. This information can augment future studies to determine the role of WDR41 and ANKRD31 genes as a candidate gene marker with desired udder and teat conformation and mastitis. Thus, it is essential to work for better udder health and prevent the incidence of mastitis in the herd.